Sistem Informasi Kursus Musik Di Inggou Victory Pematangsiantar - Agustinus Liberty Pasaribu; Irfan Sudahri Damanik; Ilham Syahputra Saragih (LPPM STIKOM Tunas Bangsa, 2021)
Inggou Victory is a non-academic institution that runs a business in providing teaching and art development in terms of music, choir, and vocals in Pematangsiantar city. Inggou Victory as an art platform in Pematangsiantar City tries to present this by more actively opening registrations for private music and vocal classes. In practice, the Admin as an employee still uses conventional methods in recording scheduling using paper which is considered less effective especially in industry 4.0 and wastes a lot of paper. Therefore, this thesis writing aims to design and create a Website-based Information System and can be presented and implemented in the company's work scope. The development and manufacture of the system is used with the Rapid Application Development (RAD) model where this RAD presents a development stage that is quite fast and dynamic compared to other conventional methods.